Revised multi-choice goal programming for integrated supply chain design and dynamic virtual cell formation with fuzzy parameters - Paydar, Mohammad Mahdi; Saidi-Mehrabad, Mohammad (International journal of computer integrated manufacturing, 2015)
Cell formation, as one of the most important decision problems in designing a cellular manufacturing system, includes grouping machines in cells and the parts as part families. In a dynamic environment, the part demand/mix change is considered over a planning horizon divided to several periods. So, the cell formation for one period may no longer be effective for future periods and hence reconfiguration of cells is essential. Due to the variation of demand and necessity of cells reconfiguration, virtual cell formation concept is introduced by researchers to take the advantage of cell formation without reconfiguration charges. On the other hand, Simultaneous consideration of supply chain and cell formation results in lower distribution and procurement costs and faster response to customers. In this paper, a new bi-objective possibilistic optimisation mathematical model is developed for integrating procurement, production and distribution planning considering various conflicting objectives simultaneously as well as the imprecise nature of some critical parameters such as customer demands and machine capacities. Then, a revised multi-choice goal programming approach is applied to solve the proposed mathematical model and to find a preferred compromise solution. Moreover, a real-world industrial case is provided to validate how the proposed model works.